2018
DOI: 10.1108/jes-05-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting profitability in Malaysia

Abstract: Purpose The purpose of this paper is to examine the factors affecting profitability in Malaysian-listed companies. It has been argued that profitability is the main pillar for any company to survive in the long run. Although profitability is the primary goal of all business ventures, scant attention has been paid to the factors that affect profitability in developing countries. This study investigates the factors affecting profitability in Malaysian-listed companies. Design/methodology/approach This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
243
4
30

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(310 citation statements)
references
References 49 publications
33
243
4
30
Order By: Relevance
“…For example, Gill et al (2010) analyzed manufacturing firms listed on the New York Stock Exchange and found a positive association between the CCC and firm profitability. These research results were substantiated by the findings of Alarussi and Alhaderi (2018), who find a strong positive relationship between working capital, firm size, company efficiency and profitability.…”
Section: Alternative Wcm School Of Thoughtsupporting
confidence: 52%
“…For example, Gill et al (2010) analyzed manufacturing firms listed on the New York Stock Exchange and found a positive association between the CCC and firm profitability. These research results were substantiated by the findings of Alarussi and Alhaderi (2018), who find a strong positive relationship between working capital, firm size, company efficiency and profitability.…”
Section: Alternative Wcm School Of Thoughtsupporting
confidence: 52%
“…O 'Neill and Mattila (2006) in their research in US hotels found that hotel profit is highly correlated with size, market segment, and occupancy percentages. A follow-up study in Malaysia (Alarussi & Alhaderi, 2018) confirmed the correlation between organisation size and profitability. Nanda and Panda (2018) differentiated the profitability determinants into two main factors, i.e.…”
Section: Hotel Profitability Determinantsmentioning
confidence: 82%
“…It has been argued that profitability is one of the main pillars for any hotel to survive in the long run. Even though profitability is a prime goal for all business leaders, it is suggested that insufficient attention has been paid to exploring drivers of profitability, especially in developing countries (Alarussi & Alhaderi, 2018). Therefore, the novelty of this empirical study consists of the inclusion of both controlled and uncontrolled determinants of hotel profitability.…”
Section: Introductionmentioning
confidence: 99%
“…H 5 : operating cash flow has a significant effect on the profitability Talk about the marketing expense; it will vary depending on how big the firm size. The increasing firm size provides greater improvement in manag- Volume 22, Issue 4, October 2018: 625-642 | 632 | ing the sales of the company and leads to higher profitability (Anderson-MacDonald, 2014;Alarussi & Alhaderi, 2017). According to Niresh & Velnampy (2014), the firm size will describe the amount, and the variety of production capacity also will show the ability of the firm to provide concurrently to its customers.…”
Section: Jurnal Keuangan Dan Perbankan | Financementioning
confidence: 99%
“…The firms may require external funding for capital expansion if the cash flow from operation does not match. Operating cash flow is related to main business activities (Alarussi & Alhaderi, 2017). For example: selling inventory, purchasing inventory, paying salaries of the employee, and providing good services.…”
Section: Sunk Cost Dilemma Behavior: the Contribution Marketing Expenmentioning
confidence: 99%